Early Start of the Dangling Procedure in Lower Extremity Free Flap Reconstruction does not Affect the Clinical Outcome - Jokuszies, A.; Neubert, N.; Herold, C.; Vogt, P. M. (Journal of Reconstructive Microsurgery, 2013)
Flap loss due to postoperative flap edema and thrombosis of the anastomosis remains the predominant concern of reconstructive microsurgeons. Due to the lack of scientific evidence, there is no unanimous opinion on when to mobilize a reconstructed lower extremity, reflecting the uncertainty of plastic surgeons regarding the effect of the dangling procedure on flap microcirculation.Patients and Methods In this randomized controlled clinical trial, we included 31 patients undergoing free flap transfer to the lower extremity.The patients were randomly divided into two groups. Cohort I consisted of 15 patients starting the dangling procedure at day 7, and cohort II consisted of 16 patients in which an early aggressive postoperative dependency started at day 3.Wrapping and dangling of the flap was performed primarily with a duration of 5 minutes three times a day and increased daily by doubling the duration over a period of 4 days, reaching 60 minutes at day 5.Before and immediately after each dangling procedure the flaps were clinically monitored under direct observation for color, capillary refill, venous congestion, flap turgor, and flap temperature.Results In all cases the postoperative course was uneventful, resulting in a success rate of 100%. No adverse effects or flap compromise were seen due to the combined dangling/wrapping procedure.Conclusion An early and aggressive start of a combined dangling/wrapping procedure does not compromise flap circulation and allows mobilizing patients after free flap transfer to the lower extremity at an early stage. This approach improves patient comfort, shortens the hospital stay, and therefore reduces socioeconomic costs.
Keywords: dangling; microcirculation; lower extremity; free flap; prospective study; randomized